Pengaruh Struktur Kepemilikan terhadap Kinerja Perusahaan dengan Praktek Good Corporate Governance sebagai Variabel Pemediasi dalam Pemeringkatan CGPI 2012 dan 2013 - Tantri Dwidarnanda Wulandari; Theresia Purbandari; Intan Immanuela (Fakultas Bisnis, 2015)
The purpose of this research is to demonstrate empirically the effect of ownership structure on firm performance, the effect of ownership on GCG, the effect of GCG on firm performance, and GCG as the mediating between ownership structure and firm performance. This research used secondary data that taken from the official website of the Indonesia Stock Exchange. The sample of this research were most companies that listed in Indonesia Stock Exchange and listed in CGPI in 2012 and 2013, by using purposive sampling technique. Hypotheses are tested using SPSS software. This research found evidence that the ownership structure has no effect on firm performance (ROA and ROS) and GCG, while GCG doesn’t improve the firm performance with size of the ROA, but significant positive effect on ROS. GCG is not able to mediate the ownership structure toward firm performance in the size of the ROA and ROS.